Optimal control in ecology and environmental protection based on quantum computing - Muhamediyeva D. T.; Mamatov N. S.; Raupova M. H.; Mukhtarova Donata; Kholiyorov Umirzok (E3S Web of Conferences)
The article considers the solution of the optimal control tasks in ecology and environmental protection based on quantum computing. Pollution dynamics are investigated, with natural decay, diffusion and controlled remediation treatments being considered. Optimal control is designed to minimize environmental impact while also minimizing the costs of cleaning up the environment. To solve the problem effectively, a quantum optimization algorithm is proposed. For this, the desired problem is transformed into a quadratic optimization problem. This enables the application of quantum computing to the formulation of optimal policies for environmental regulation. Experiments are performed, a comparison is made between quantum-classical approaches and conventional techniques, and the feasibility of quantum optimization in sustainability issues is debated.